Adam Watkins Climbs Out of His Crib - Watkins, Howard::::::::: (1980)
Adam Watkins successfully climbs over crib footboard landing on orange checkered baby blanket and toy box with Christine Watkins nearby Baby blanket made by Frances Kamp